HUBUNGAN DUKUNGAN KELUARGA DENGAN MOTIVASI PENYUSUNAN SKRIPSI PADA MAHASISWA - Endang Sawitri; Marlina Fitriani; marwanti; Agus Murtana (Universitas Muhammadiyah Klaten, 2026)
Final-year students often face obstacles in completing their thesis, such as difficulties in determining the title, lack of references, communication barriers with lecturers, and poor time management. Family support is an important factor in increasing students’ motivation and self-confidence. This study aims to determine the relationship between family support and thesis-writing motivation among final-year undergraduate nursing students at Muhammadiyah University of Klaten. This research employed a quantitative approach with a cross-sectional method. Respondents were selected using total sampling, consisting of 72 students who met the exclusion criteria. The study was conducted among final-year undergraduate nursing students at Muhammadiyah University of Klaten, with data collection carried out over two weeks, from June 10 to June 17, 2025. The data collection instruments used were the family support questionnaire and the thesis-writing motivation questionnaire. Bivariate analysis using Kendall’s Tau test showed a significant relationship between family support and thesis-writing motivation (p-value = 0.000; r = 0.828), indicating a very strong correlation between family support and thesis-writing motivation. The findings revealed that the level of family support received by students—including emotional, informational, appraisal, and instrumental aspects—was high (44.4%), and the students’ motivation in completing their thesis—based on enthusiasm, persistence, and self-confidence—was strong (47.2%). The conclusion of this study is that there is a significant relationship between family support and thesis-writing motivation among final-year undergraduate nursing students at Muhammadiyah University of Klaten, with a correlation coefficient of 0.828.